IMPLEMENTASI NILAI NILAI PANCASILA DAN IMPLIKASINYA TERHADAP MAHASISWA SEBAGAI “AGENT OF CHANGE” - Prambudi, Yunike Dita; Najicha, Fatma Ulfatun (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2022)
Indonesia is a unitary state consisting of various tribes and nations based on Pancasila as the basis of the state. Pancasila as the basis of the state must be implicated and realized in all community actions, including in tertiary institutions. Higher Education was formed in the context of educating the nation's life through students who have character in them, Students have a role as